Strategii de comunicare în familiile cu copii adoptați - Buzducea, Doru; Lazăr, Florin; Grigoraș, Vlad (Calitatea Vieții, 2014)
In the first decade after the fall of the communist regime in 1989, Romania was one of the major sending countries for inter-country adoptions, As a result of external pressures, after 2001, domestic adoptions became prevalent, and since 2004, no international adoption took place. In recent years, studies on domestic adoptions flourished, but none investigated how adoptive families disclose to the child that he/she is adopted. In 2012, a new legislation on adoption required adoptive families to disclose to the child that is adopted, this topic being also included in the curriculum preparing families for adoption. The present study investigated adoption disclosure practices of Romanian adoptive families in a nationally representative sample of domestic adoptions carried out between 2000–2009 (N= 516). The research was carried out with the support of the National Office for Adoptions, local Departments for Social Work and Child Protection and UNICEF. While a great majority of families (95%) agree with adoption disclosure, only 69% disclosed. One in ten families looked for support to disclose. The mean age of the children at disclosure was 5 years, families from rural areas being more open than those from urban areas (73% vs. 67%). A very small proportion of children are in contact with the biological family, and mostly with their brothers and sisters than with the parents. More than two thirds (69%) of the families who experienced reunification with the biological family (10% of total sample) had a positive experience. Adoptive families do not tend to agree with open adoptions. Post-adoption social services need to be further developed to support families and children on disclosure strategies and/or reunification, if wanted. Requiring adoptive families to disclose to the child seems to remain a controversial issue in Romania, and open adoption is not too popular, but positive examples can be used.